Graduates' Attitudes to Research Skill Development in Undergraduate Media Education. (June 2016) - Wilmore, Michael; Willison, John
This article examines the attitudes of graduates employed in different segments of the media industry to the development of research skills during their studies. Qualitative interviews were conducted with ten graduates employed in different jobs approximately one year after graduation to understand how applicable they found generic and media-specific research skills to their employment. The study was conducted as part of a wider project evaluating the application of a systematic framework for research skills development, across whole degree programmes. The interviews demonstrate broad agreement regarding the value of research skills for media employment. However, there were divergent opinions about the need to articulate research skills explicitly and the value of media-specific skill for current employment situations. Interviewees also indicated varying levels of awareness regarding the relevance research skills have across different employment contexts. Therefore, it is important that media-educators understand how their students' differing career destinations immediately after graduation influence formal and informal evaluations of the quality of their course. We conclude that this educational challenge is best addressed by implementing a consistent framework for research education that improves students' metacognitive awareness of the transferability of this graduate attribute across multiple industries and career destinations.